Internalization of Islamic Values in Madrasah Ibtidaiyah's General Lessons in Developing Students' Morals - M Dahlan R; Zainal Arief; Noor Isna Alfaien; Rosmawati Binti Mohamad Rashit (Program Studi PGMI UIN Salatiga, 2022)
The identification of madrasah as an Islamic school is a reflection of Islamic education itself, which leads to the goal of Islamic education, namely the formation of morals by internalization. Madrasah Ibtidaiyah is an educational institution that is characterized by Islam, but in the learning process it does not only teach religious subjects but also general subjects. The methodology used in this study is descriptive with a post-positivist approach, with purposive sampling for determining data sources, in-depth interviews as data collection, and Miles and Huberman's theory for analysis. The findings revealed that internalization of Islamic values in the formation of students' morality tends to be religious, independent, social, environmental, tolerant, and friendship related at Madrasah Ibtidaiyah. This study suggests that Madrasah Ibtidaiyah be used to realize and familiarize morals, with teachers serving as role models and being on the front lines of moral implementation.